Numerical modeling of a high magnitude debris-flow event occurred in Brazil - dos Santos Corrêa, Claudia Vanessa [UNESP]; Reis, Fábio Augusto Gomes Vieira [UNESP]; do Carmo Giordano, Lucília [UNESP]; Cabral, Victor Carvalho [UNESP]; Veloso, Vinícius Queiroz [UNESP]; D’Affonseca, Fernando Mazo (Springer Nature, 2024)
Debris flows are rapid downslope, gravity-driven movements of highly viscous, dense and concentrated/hyperconcentrated fluid materials. In Brazil, the most susceptible area to this type of mass movement comprises the oriented foothills of Serra do Mar. Several numerical modeling approaches have been created to measure, identify, predict, and monitor debris-flow processes, for example, RAMMS (Rapid mass movement simulation), a single-phase numerical model that simulates the propagation of debris flow using the Voelmy rheology. In this work, the RAMMS code is applied to model the debris-flow event that occurred in 1967 in Caraguatatuba County (State of Sao Paulo). Induced by heavy rains, this debris-flow event is one of highest magnitude recorded in Brazil, with more than 100 deaths and major socioeconomic and environmental impacts. Studies involving debris-flow modeling are still recent in Brazil, and they are relevant because can be applied to support the delineation of the affected area and the understanding of the dynamics of these phenomena. Thus, back-analysis studies are applied to assist the model setup and the results evaluations. Field observations and the back-analysis studies showed that the debris-flow processes in the Serra do Mar region are strictly granular, which helped the modeling step, and the debris are preferentially deposited in regions with low slopes (< 5°). The model results can be used to support political and engineering actions aimed at mitigating the effects of future events.
Keywords: Back-analysis studies; Debris flow; RAMMS; Serra do Mar